A Trip to the Himalayas - Naidu, M. Kamal (International Journal of Bio-resource and Stress Management, 2023)
Owing to its awesome beauty and rich biodiversity coupled with a sense of spirituality the Himalaya has always been one of the most desired destinations for people around the world. For India, the Himalaya is the home of god Shiva and considered as the sacred place where many saints and sages did meditation to realize the Ultimate Truth and for salvation. Being an Indian Forest Service officer, the author shares his experiences of divine serenity on his trip to various parts of the great Himalayas. The paper also describes about the flora and faunal diversity of the region.